PENINGKATAN PRODUKSI MELALUI PEMBERDAYAAN UKM DI KECAMATAN TUGU KOTA SEMARANG - Wyati Saddewisasi; Aprih Santoso; Sri Yuni Widowati; Teguh Ariefiantoro; Indarto Indarto (Publisher UPT P2M Politeknik Negeri Malang, 2017)
SMEs in Tugu District with a total membership of 130 people. The business group is expected to grow business unit. One of the benchmarks for the development of business groups is the increasing number of products accompanied by increased operating revenues. In order for the number of products to increase, then increased production needs to be run. Increased production can be done through various ways, among others, through business empowerment. However, in the effort of SME business development still encountered many obstacles such as: not yet the formulation of business development strategy and data base profile of each business unit; increased production and business development has not been reached; lack of clarity on financing for business assistance; and the need for cooperation in the field coaching. In overcoming some of these obstacles required the existence of business empowerment that aims to develop SMEs in the District Tugu. Community service activity aims to improve the skill of human resources of entrepreneur (SME in Kecamatan Tugu) about the procedure of developing business and supply of raw materials and doing simple bookkeeping. This activity is carried out by providing knowledge on business management and business analysis. Besides, also introduced raw material sources and simple bookkeeping. Training and counseling is provided directly to business groups on business management, business analysis and simple bookkeeping. It is also given knowledge about determining the source of raw materials.